PrEP Use Among Female Sex Workers: No Evidence for Risk Compensation - AFFOLABI, DISSOU (My University, 2019)
Background: Little is known about risk compensation among female sex workers (FSW) on HIV pre-exposure prophylaxis (PrEP), and self-report of sexual behaviors is subject to bias. Setting: Prospective observational PrEP demonstration study conducted among FSW in Cotonou, Benin. Methods: Over a period of 24 months, we assessed and compared trends in unprotected sex as measured by self-report (last 2 or 14 days), by detection of sexually transmitted infections (STIs), and by vaginal detection of prostate-specific antigen and Y-chromosomal DNA, 2 biomarkers of semen exposure in the last 2 or 14 days, respectively. Trends were assessed and compared using a log-binomial regression that was simultaneously fit for all unprotected sex measures. Results: Of 255 participants, 120 (47.1%) completed their follow-up. Prevalence of STI decreased from 15.8% (95% confidence interval: 11.8% to 21.0%) at baseline to 2.1% (95% confidence interval: 0.4% to 10.2%) at 24 months of follow-up (P-trend = 0.04). However, we observed no trend in self-report of unprotected sex in the last 2 (P = 0.42) or 14 days (P = 0.49), nor in prostate-specific antigen (P = 0.53) or Y chromosomal DNA (P = 0.25) over the same period. We observed no statistically significant difference between trends in self-report of unprotected sex and trends in biomarkers of semen exposure in the last 2 days (P = 0.14) or in the last 14 days (P = 0.29). Conclusions: We observed no evidence of risk compensation, and a decrease in STI among FSW on PrEP. PrEP intervention may be an opportunity to control STI among FSW. Future studies should assess risk compensation with biomarkers of semen exposure when possible.
Keywords: PrEP; sexual behavior; sex workers/prostitutes; prostate-specific antigen; Y-chromosomal DNA; HIV